Technology and Livelihood Education Learning Brochures for Grade 7 Students - John Paul C. Demapendan; Emily Anne T. Aquino; Gracelle P. Hilario (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: The study focuses on developing and evaluating Technology and Livelihood Education (TLE) brochures for 7th-grade students, aiming to address educational gaps specifically lack of instructional materials among TLE exploratory subjects. Methodology: The methodology involved a needs assessment survey to identify the least learned competencies in TLE 7. Select experts evaluated criteria such as design, standards alignment, content quality, and ease of use. The suggestions and recommendations were thematically analyzed to improve the learning brochures further. Cost analysis was employed to determine the cost of producing the learning materials. Main Findings: Expert evaluations rated the brochures highly across design, standards alignment, content quality, and ease of use, with recommendations for improving graphic elements and layout consistency. The cost analysis confirmed the affordability and local availability of production materials. Additionally, a proposed Instructional Brochure Development Framework was introduced, encompassing five phases: Conceptualization, Designing, Development, Evaluation, and Refinement. Novelty/Originality of this study: The study advocates the use of learning brochures as instructional material in Technology and Livelihood Education and proposes an Instructional Brochure Development Framework for designing and developing learning brochures for other subjects.